ANALISIS BEBAN PENCEMAR DAN KAPASITAS ASIMILASI LOGAM BERAT DI PERAIRAN SUNGAI SETINGKAI KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Hasdi Yanti HS; Yusni Ikhwan Siregar; Sofia Anita (Jurnal Ilmu Lingkungan, 2014)
The Research on analysis of pollutant loading and heavy metal assimilation capacitiesin waters of Setingkai River subdistrict of Kampar Kiri Regency of Kampar has beenheld for three months (March to May 2013) by using survey methods, that was directlymeasure on the object to be studied (in situ) and laboratory test (ex-situ). Samples weretaken at four sites purposively by considering the location of the pollutants inputsources, the influx and the distance between sampling locations. The parameters ofheavy metals studied were Pb, Cu and Zn with data analysis including: descriptiveanalysis, pollutant load analysis, assimilation capacities analysis refers to the PP No.82 year 2001 class II. The Result of research showed that the activity of PETI along theflow of Setingkai River have degraded water quality parameters of colour, brightness,TSS, DO, COD and heavy metals such as Pb, Cu and Zn. Average estimation results ofmetal pollutant load Zn 54,10 tons/month; Pb 8,39 tons/month and Cu 7,12 tons/month.The assimilation capacities calculation showed that Zn pollutant load is higher thanwaters assimilation capacities (BP = 54,10 tons/month > KA = 0,0041 ton/month), Pb(BP = 8,39 tons/month > KA = 5,28 tons/month) and Cu (BP = 7,12 tons/month > KA= 1,41 tons/month). The result of research showed that the current condition ofSetingkai river has tainted of Zn, Pb and Cu and hazardous to waters bioticenvironment and also human health.